123k views
1 vote
Use the steps to finish writing an equivalent equation for y in terms of x. −6x = 12 − 4y 1.  Subtract 12 from both sides: −6x − 12 = −4y 2.  Divide −4 to both sides: −6x − 12 −4 = −4y −4 x + 3 = y

User Mark Homer
by
5.6k points

2 Answers

6 votes

Answer:

1.5x + 3 = y

Explanation:

−6x = 12 − 4y

1. Subtract 12 from both sides: −6x − 12 = −4y

2. Divide −4 to both sides: -6x-12 over -4 = -4y over -4

User Cjbrog
by
6.5k points
2 votes

Answer: 1.5x

Explanation:

User Carlos Garces
by
6.0k points